Apple-shaped obesity: A risky soil for cytokine-accelerated severity in COVID-19 - Hosoya, Tadashi; Oba, Seiya; Komiya, Yoji; Kawata, Daisuke; Kamiya, Mari; Iwai, Hideyuki; Miyamoto, Sho; Kataoka, Michiyo; Tobiume, Minoru; Kanno, Takayuki; Ainai, Akira; Sato, Hiroyuki; et al. (Proceedings of the National Academy of Sciences - PNAS, 2023)
Obesity has been recognized as one of the most significant risk factors for the deterioration and mortality associated with COVID-19, but the significance of obesity itself differs among ethnicity. Multifactored analysis of our single institute–based retrospective cohort revealed that high visceral adipose tissue (VAT) burden, but not other obesity-associated markers, was related to accelerated inflammatory responses and the mortality of Japanese COVID-19 patients. To elucidate the mechanisms how VAT-dominant obesity induces severe inflammation after severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection, we infected two different strains of obese mice, C57BL/6JHamSlc-ob/ob (ob/ob), C57BLKS/J-db/db (db/db), genetically impaired in the leptin ligand and receptor, respectively, and control C57BL/6 mice with mouse-adapted SARS-CoV-2. Here, we revealed that VAT-dominant ob/ob mice were extremely more vulnerable to SARS-CoV-2 due to excessive inflammatory responses when compared to SAT-dominant db/db mice. In fact, SARS-CoV-2 genome and proteins were more abundant in the lungs of ob/ob mice, engulfed in macrophages, resulting in increased cytokine production including interleukin (IL)-6. Both an anti-IL-6 receptor antibody treatment and the prevention of obesity by leptin replenishment improved the survival of SARS-CoV-2-infected ob/ob mice by reducing the viral protein burden and excessive immune responses. Our results have proposed unique insights and clues on how obesity increases the risk of cytokine storm and death in patients with COVID-19. Moreover, earlier administration of antiinflammatory therapeutics including anti-IL-6R antibody to VAT-dominant patients might improve clinical outcome and stratification of the treatment for COVID-19, at least in Japanese patients.